Complete-Lattice Morphisms Compatible with Closure Operators: Josef Slapal - Team, Support (Thai Journal of Mathematics, 2010)
We introduce and study certain morphisms between complete lattices. We investigate three kinds of compatibility of these morphisms with closure operators on complete lattices.